Synthesis of a New Type of Trans-Decalin Vitamin D Analogue through a Dyotropic Ring Expansion - Hugo Santalla; Uxía Gómez-Bouzó; Irene Sánchez-Sanz; Yagamare Fall (Journal of Chemistry)
A new vitamin D analogue with a trans-fused decalin as the CD-ring system and containing a sulphur atom in the side chain has been synthesized in our research group. The obtention of this analogue is based on a recently discovered transformation of hydrindane cores into decalins through a dyotropic ring expansion in very mild conditions.